The influence of platelet-derived products on angiogenesis and tissue repair: a concise update - Martínez, Constanza E.; Smith, Patricio C.; Palma Alvarado, Verónica A. (Frontiers in Physiology, 2015)
Platelet degranulation allows the release of a large amount of soluble mediators, is an essential step for wound healing initiation, and stimulates clotting and angiogenesis. The latter process is one of the most critical biological events observed during tissue repair,  increasing the growth of blood vessels in the maturing wound. Angiogenesis requires the  action of a variety of growth factors that act in an appropriate physiological ratio to assure  functional blood vessel restoration. Platelets release main regulators of angiogenesis: Vascular Endothelial Growth Factors (VEGFs), basic fibroblast growth factor (FGF-2), and Platelet derived growth factors (PDGFs), among others. In order to stimulate tissue repair, platelet derived fractions have  been used as an autologous source of growth factors and biomolecules,  namely Platelet Rich Plasma (PRP), Platelet Poor Plasma (PPP) and Platelet Rich Fibrin   (PRF). The continuous release of these growth factors has been proposed to promote  angiogenesis both in vitro and in vivo. Considering the existence of clinical trials currently evaluating the efficacy of autologous PRP, the present review analyses fundamental questions  regarding the putative role of platelet derived fractions as regulators of angiogenesis and evaluates the possible clinical implications of these formulations.